Professional quality of life and burnout among medical physicists working in radiation oncology: The role of alexithymia and empathy. (July 2020) - Di Tella, Marialaura; Tesio, Valentina; Bertholet, Jenny; Gasnier, Anne; Gonzalez del Portillo, Elisabet; Spalek, Mateusz; Bibault, Jean-Emmanuel; Borst, Gerben; Van Elmpt, Wouter; Thorwarth, Daniela; Mullaney, Laura; Røe Redalen, Kathrine; et al.
Highlights: Burnout is critical for oncology professionals, affecting quality of life and performance at work. Alexithymia and empathy are personality traits influencing the capacity to cope with stress. Alexithymia increases burnout among medical physicists with a negative impact at work. Higher level of empathy are correlated to a better professional quality of life. This data may help identifying subjects at risk to implement preventive strategies. Abstract: Background and purpose: The professional quality of life of radiation oncology professionals can be influenced by different contributing factors, including personality traits. Alexithymia involves deficits in emotion processing and awareness. Empathy is the ability to understand another's 'state of mind/emotion'. We investigated professional quality of life, including burnout, in radiation oncology, exploring the role of alexithymia and empathy and targeting the population of medical physicists (MPs), since this professional category is usually underrepresented in surveys exploring professional well-being in radiation oncology and MPs may experience professional distress given the increasing complexity of multimodal cancer care. Material and methods: An online survey was addressed to ESTRO members. Participants filled out three questionnaires to evaluate alexithymia, empathy and professional quality of life: a) Toronto Alexithymia Scale (TAS-20); b) Interpersonal Reactivity Index (IRI); c) Professional Quality of Life Scale (ProQoL). Professional quality of life as per ProQoL was considered as dependent variable. The three domains of the ProQoL, namely compassion satisfaction (CS), secondary traumatic stress (STS) and burnout were correlated with alexithymia (as per TAS-20) and empathy (as per IRI with three subcategories: empathic concern, perspective taking and personal distress) and demographic/professional characteristics as independent variables. Generalized linear modeling was used. Significant covariates on univariate linear regression analysis were included in the multivariate linear regression model. Results: A total of 308 medical physicists completed all questionnaires. Alexithymia as per TAS-20 was correlated to decreased CS ( β  = −0.25, p  < 0 0.001), increased likelihood for STS ( β  = 0.26, p  < 0 0.001) and burnout ( β  = 0.47, p  < 0 0.001). With respect to empathy, the 'Empatic Concern' subscale of the IRI was found to be a significant predictor for increased CS ( β  = 0.19, p  = 0 0.001) and increased STS ( β  = 0.19, p  < 0 0.001), without significant correlation with burnout. The individual's perception of being valued by own's supervisor was correlated to increased CS ( β  = 0.23, p  < 0.001), and decreased burnout ( β  = −0.29, p  < 0.001). Conclusions: Alexithymic personality trait increased the likelihood to develop burnout, with less professional satisfaction amongst MPs working in radiation oncology. Empathy results in higher professional fulfilment. These results may be used to benchmark preventing strategies, including peer support, debriefing sessions, leadership initiatives and work-load limitation strategies.